2016
DOI: 10.1111/gcb.13366
|View full text |Cite
|
Sign up to set email alerts
|

Highest drought sensitivity and lowest resistance to growth suppression are found in the range core of the treeFagus sylvaticaL. not the equatorial range edge

Abstract: Highest drought sensitivity and lowest resistance to growth suppression are found in the range core of the tree Fagus sylvatica L. not the equatorial range edge AbstractBiogeographical and ecological theory suggests that species distributions should be driven to higher altitudes and latitudes as global temperatures rise. Such changes occur as growth improves at the poleward edge of a species distribution and declines at the range edge in the opposite or equatorial direction, mirrored by changes in the establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
153
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(191 citation statements)
references
References 119 publications
21
153
6
Order By: Relevance
“…Consequently, populations at the range edge do not appear to be climate-sensitive because they are already absent from climatically marginal sites. In essence, at the equatorial range edge many sampled populations are already ''climate relicts, occupying locations where local features interact to ameliorate the regional climate'' (Cavin and Jump 2016;Hampe and Jump 2011). In contrast, more frequently benign conditions in the distribution core allow the species to occupy (and be sampled at) a wider range of environments, and consequently, the species displays similar climate signals present at the range edge, despite a less extreme regional climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, populations at the range edge do not appear to be climate-sensitive because they are already absent from climatically marginal sites. In essence, at the equatorial range edge many sampled populations are already ''climate relicts, occupying locations where local features interact to ameliorate the regional climate'' (Cavin and Jump 2016;Hampe and Jump 2011). In contrast, more frequently benign conditions in the distribution core allow the species to occupy (and be sampled at) a wider range of environments, and consequently, the species displays similar climate signals present at the range edge, despite a less extreme regional climate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tree-rings can be used to quantify the sensitivity of forest growth to climate and monitor the response of forests to environmental changes over recent decades (Dobbertin 2005;Fritts 1966;Jump et al 2006). Furthermore, networks of tree-ring chronologies from across species' distributions can be used to identify populations that have higher or lower sensitivity to predict future climate changes, either using measurement of growth trends (Cavin and Jump 2016;Galvan et al 2014) or by comparing the strength of growth-climate relationships (Carrer et al 2010). Analysis of tree-ring chronologies may therefore be utilised to identify potential sources of provenances that are preadapted to climatic conditions predicted for the future, improve predictions of the impact of climate change on forest ecosystem services that are dependent on forest growth or inform efforts to conserve forest-based biodiversity (Dobbertin 2005;Gessler et al 2007;Zimmermann et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Van der Werf et al (2007), for example, observed that growth of beech ceased during the extreme dry year 2003, but that it quickly recovered thereafter. In a future warmer climate, drought impacts are likely to become more severe, and may be particularly pronounced in the core of the species range as suggested by Cavin and Jump (2016). In their recent network study on beech, highest sensitivity and low resistance to drought is namely reported in the core of the species range, while dry range edge populations were characterized by particularly high drought resistance.…”
Section: Introductionmentioning
confidence: 94%
“…Thereby, it helps to reduce climate change induced risks and uncertainties associated with forest and water management decisions and ecosystem services (Cavin & Jump, 2016;Chu et al, 2016;IPCC, 2012;Lapointe-Garant et al, 2010;Schongart et al, 2006;Subedi & Sharma, 2013). Such information is highly required to better project the impacts of climate change on biological and ecological systems.…”
Section: Remote Climate Forcing Of Rainfall On the Bluementioning
confidence: 99%